Efecto de la vegetación y la estacionalidad hidrológica en la diversidad de aves de la ciudad de Iquitos, Perú - Angulo Pérez, Natalia Carolina (2022)
The study of birds and vegetation in Amazonian cities is important because it provide guidelines that help solve environmental quality problems in a city. Therefore, the methods of counting by points and plots, satellite images and bibliographic review were used, to know the diversity of birds and vegetation in urban environments with different levels of tree cover, compare their diversity in times of floods and time of droughts of rivers and relate their parameters with those of vegetation and hydrological seasonality in Iquitos city. 127 species of birds were recorded (113 growing and 107 emptying of rivers) and 117 plant species. There was a greater richness of birds in streets on river banks and greater richness of plants and tree cover in streets with many green areas. The most abundant and dominant birds were Coragyps atratus, Brotogeris versicolurus and Columba livia and in plants they were Adonidia merrillii and Cecropia membranacea. Bird diversity differs significantly in times of floods and time of droughts and is related to plant species richness, native plants, exotic plants, trees, palms, shrubs, herbs, tree cover, distance from the transect to a matrix of continuous forest or river and precipitation, so greater diversity and tree cover will help to have more bird species, which will allow the development of an urban birdwatching program to generate jobs and improve economic income in the city.